2008
DOI: 10.1007/s00423-008-0384-5
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative PTH monitoring during parathyroidectomy: the need for stricter criteria to detect multiglandular disease

Abstract: Despite the higher rate of unnecessary bilateral exploration, our criteria results in a lower FP, markedly reducing the risk of missing multiglandular disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
45
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(49 citation statements)
references
References 33 publications
(58 reference statements)
0
45
0
4
Order By: Relevance
“…Such an increase in the number of FN predictions has been described by many investigators, including our own data analysis. Lombardi et al was able to decrease the rate of FP results of IOPTH from 2.4% when using Miami criterion to 0.5% when using Rome criterion, which means an improved success rate of primary operation, but at the cost of the FN results rate increased by 11% [14]. This implies a potential increase in operative time, overall costs, and morbidity rate.…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Such an increase in the number of FN predictions has been described by many investigators, including our own data analysis. Lombardi et al was able to decrease the rate of FP results of IOPTH from 2.4% when using Miami criterion to 0.5% when using Rome criterion, which means an improved success rate of primary operation, but at the cost of the FN results rate increased by 11% [14]. This implies a potential increase in operative time, overall costs, and morbidity rate.…”
Section: Discussionmentioning
confidence: 95%
“…Rome criterion An iPTH decay greater than 50% from the highest preexcision level, and/or iPTH concentration within the reference range at 20 min postexcision, and/or ≤7.5 ng/L lower than the value at 10 min postexcision predicts cure from the hyperparathyroid state [14].…”
Section: Iopth Interpretation Criteriamentioning
confidence: 99%
See 1 more Smart Citation
“…However, other authors have reported error rates as high as 16% due to false-negative and false-positive results (18). They suggested that 20 min of PTH monitoring should be performed (19). In this study, we performed IOPTH monitoring after 10 min if a >50% drop of PTH levels was not observed.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, selective venous sampling with iPTH estimation was found useful in regionalization of hypersecreting parathyroid tissue in cases of recurrent or persistent disease [15,16]. Moreover, it has become possible to intraoperatively monitor the quality of surgical treatment by intraoperative serum parathormone assay (IOPTH) [17][18][19][20]. Several groups have also tested the utility of intraoperative bilateral internal jugular venous (BIJV) sampling with IOPTH in lateralizing the side of the neck harboring a parathyroid adenoma with promising results [13,21].…”
Section: Introductionmentioning
confidence: 99%